Supplier performance measurement in discrete manufacturing industry-empirical study on Indian manufacturing sector - Mohanty, Manoj Kumar; Gahan, Padmabati (Journal of Business Economics and Management, 2013)
Suppliers are the value creators for the organizations and have emerged as value-adding partners in industrial relationships since last two decades. These values can be derived effectively given the buying organizations keep a long-term strategic relationship with high performing suppliers. To measure the performance organizations have to decide the performance parameters depending on the nature of business and their specific needs from the supply base. The current discrete manufacturing industries of India judging the performance of the suppliers based on technical capability, cost, delivery, quality & regulatory adherence for safety and environment. But from the larger interest of the manufacturing industry more relevant attributes are needs to be considered, which are explored from our research are responsiveness of the supplier, effectiveness of the aftersales service, delivery flexibility, documentation ability, trust & commitments. All these performance measurement attributes will drive effectiveness and efficiency of the supply chain.First published online: 19 Oct 2012